Kaposi's Varicelliform Eruption in Atopic Dermatitis treated with Korean medicine - Dong-Jin Lee; Kang Kwon; Hyung-Sik Seo; Seung-Ho Sun (Korean Pharmacopuncture Institute, 2014)
Objectives:This case report is to present a complete recovery from Kaposi's varicelliform eruption (KVE) that occurred in a patient with atopic dermatitis by applying Korean Medicine therapies. Methods:Hwangyeonhaedoktang pharmacopuncture (HP), 0.3 mL, and 25% bee venom pharmacopuncture (BVP), 0.1 mL, were injected, 0.2 mL each, at both BL13 acupoints once a day in the morning. Acupuncture was applied at Sama Upper, Middle and Lower of the Master Tung acupuncture points and at ST44 on the left lateral for 30 minutes twice a day. The affected face was gauze dressed with mixture of 2.0 mL HP and 1.0 mL 25% BVP with 20 mL of normal saline twice a day. Herbal Medicine, Seungmagalgeuntang, was administered three times a day after each meal. Results:Rashes and papules on the face were completely cleared after 10 days of treatments. Conclusion:KVE, an acute and urgent dermatitis, can be effectively treated with Korean medicine.